Tumors with EWSR1-CREB1 and EWSR1-ATF1 fusions: the current status - Thway, Khin; Fisher, Cyril (The American journal of surgical pathology, 2012)
EWSR1-CREB1 and EWSR1-ATF1 are gene fusions of which one or both have now been consistently described in 5 histopathologically and behaviorally diverse neoplasms: angiomatoid fibrous histiocytoma, conventional clear cell sarcoma (of tendons and aponeuroses), clear cell sarcoma-like tumor of the gastrointestinal tract, hyalinizing clear cell carcinoma of the salivary gland, and primary pulmonary myxoid sarcoma. Some of the tumors in this group have been described only recently, and others have been the subject of recent genetic insights contributing to their characterization. These neoplasms are all rare; yet, the increasing frequency with which EWSR1-CREB1 and EWSR1-ATF1 fusions are being described in separate entities is noteworthy. The additional molecular mechanisms by which tumors with such variable morphologic, immunohistochemical, and clinical phenotypes are generated are yet to be understood. We review the clinicopathologic and molecular features of this group of neoplasms unified by the presence of EWSR1-CREB1 and EWSR1-ATF1 genetic fusions.